Skill Sets and Competencies of Chief Financial Officers (CFOs) in India - Thomas , Rejoice (International Journal of Psychosocial Rehabilitation, 2020)
The superior performance and excellence in all endeavors humankind has ever strived for, the focus has been “What are the factors/characteristics that will result in better individual behavior and performance?” Some of the factors suggested by researchers include heredity, gender, size and shape of the head, skin color, handwriting, IQ, and the list continues. With respect to work and organizational requirements, some of the skills, like technical knowledge, years of experience, educational qualifications, etc., will result in better individual behavior and performance.